Multifunction smart bag: the roseate / Arniyati Hussin ... [et al.] - Hussin, Arniyati; Shariff, Sharina; Ahmad, Nurul Zamratul Asyikin; Naseri, Roszi Naszariah Nasni; Abdul Azis, Rafidah; Azis, Siti Noraziana (Universiti Teknologi MARA, Perak, 2020)
In the modern world, the bag has been part of daily fashion and trend as many people carry a wide variety of it ranging from cloth or leather briefcases, handbags, and backpacks. The product that is actually used for storing or holding something has been a set of strong trends available in different sizes, fabrics, and shapes in order to cater high demands. Heavy and busiest daily routine activities, limited time, costsaving, and people looking for flexibility recently also trigger our team to produce the roseate bag come out with multifunction with an adjustable preference for the traveler, students, and any types of people as well that would occupy the space of bag with depends on their loads. The common design and function of the tote bag are in carrying books and stuff a person needed based on their occasion. Through Roseate bag we bring out a multifunction bag product in combining two main functions of the bag as the main purpose of a tote bag is to serve as an easy carryall, especially during those busy days spent shopping or running errands and a clothes bag is use for carrying garments also included the toiletries and any personal belonging to a person for traveling purpose. The objectives of the Roseate bag are in reducing the number of bags a person needs for themselves as they can choose either using the tote bag when they carry a book or easy carryall stuff and using it to bring their clothes as in the standard main function of a clothes bag. It helps in reducing a person's expenses and ease of mind in purchasing several bags and deciding on which bag they wanted to use.